2022
DOI: 10.3390/socsci11070281
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Greenspaces: Synthesizing Knowledge and Experience in Nova Scotia’s African-Canadian Communities through Participatory Research and SoftGIS

Abstract: Greenspaces are integral components of communities and provide numerous benefits. However, human development threatens these spaces, particularly in communities of color where histories of racial injustice persist and environmental vulnerabilities remain. A step towards preventing the loss of important cultural greenspaces is documenting knowledge and experience. This research employed community-based participatory techniques to study the relationship between the landscape and African-Canadian communities arou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 121 publications
0
6
0
Order By: Relevance
“…This means that the first two factors together account for about 57% of the total variance in the observed variables. This is generally considered an acceptable greenspaces are as follows: Zhian Park (17), Shida Park (82), Dongpo Park (18), and Wanhua Triangle Park (20) are categorized as small-sized greenspaces; Yongzhi Park (14)…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This means that the first two factors together account for about 57% of the total variance in the observed variables. This is generally considered an acceptable greenspaces are as follows: Zhian Park (17), Shida Park (82), Dongpo Park (18), and Wanhua Triangle Park (20) are categorized as small-sized greenspaces; Yongzhi Park (14)…”
Section: Resultsmentioning
confidence: 99%
“…Third, the statistical results underscore the importance of incorporating greenspaces into urban environments, not just for their aesthetic or recreational value but for their role in emphasizing a sense of belonging [14,35]. Policies and government practices that support the development of community programs along with the preservation of greenspaces can contribute to healthier and more cohesive communities for residents in densely developed urban environments.…”
Section: Retention Green Place Imagesmentioning
confidence: 89%
See 2 more Smart Citations
“…Researchers found that people regard greenspace as gathering places with family, friends or neighbors (Irvine et al, 2013;Schetke et al, 2016;Mao et al, 2020;Fisher et al, 2021;Sen and Guchhait, 2021) emphasizing that increasing social bond through the nearby natural environment prevents social isolation (Ward Thompson et al, 2016) and promotes environmental justice (Enssle and Kabisch, 2020). Especially for social minority groups, greenspace functions as a place for their unification and acculturation (leBrasseur, 2022).…”
Section: Greenspace Interactionsmentioning
confidence: 99%